If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -6) = 8 + 4n Reorder the terms: 3(-6 + n) = 8 + 4n (-6 * 3 + n * 3) = 8 + 4n (-18 + 3n) = 8 + 4n Solving -18 + 3n = 8 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -18 + 3n + -4n = 8 + 4n + -4n Combine like terms: 3n + -4n = -1n -18 + -1n = 8 + 4n + -4n Combine like terms: 4n + -4n = 0 -18 + -1n = 8 + 0 -18 + -1n = 8 Add '18' to each side of the equation. -18 + 18 + -1n = 8 + 18 Combine like terms: -18 + 18 = 0 0 + -1n = 8 + 18 -1n = 8 + 18 Combine like terms: 8 + 18 = 26 -1n = 26 Divide each side by '-1'. n = -26 Simplifying n = -26
| .75x+8=x | | 0=x*2-x-30 | | -6=y+3 | | 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 |